Flavonoids and related privileged scaffolds as potential urease inhibitors: a review. Issue 5 (23rd January 2023) - Al-Rooqi, Munirah M.; Mughal, Ehsan Ullah; Raja, Qandeel Alam; Hussein, Essam M.; Naeem, Nafeesa; Sadiq, Amina; Asghar, Basim H.; Moussa, Ziad; Ahmed, Saleh A.
Abstract : Urease is produced by some bacteria and fungi, and its inhibition has been of interest as a potential therapeutic strategy for the treatment of certain bacterial infections and urea-related disorders. Abstract : Infections caused by bacteria are a significant issue on a global scale, and imperative action is required to discover novel or improved therapeutic agents. Flavonoids are a class of plant-derived compounds that have a variety of potentially useful bioactivities. These activities include immediate antimicrobial properties, synergistic effect with antimicrobials, ferocious repression of pathogenicity, anti-urease activity etc. This review summarizes current studies concerning anti-urease actions of flavonoids as well as structural–activity correlation investigations of the flavonoid core structure. It is possible that if researchers investigate the many structural changes that may be made in flavonoid rings, they'll be able to build up novel compounds that have powerful and effective anti-urease properties.